Chronic variable stress leads to sex specific gut microbiome alterations in mice - Dawson R. Kropp; Jennifer R. Rainville; Matthew E. Glover; Mariya Tsyglakova; Rupabali Samanta; Tamer R. Hage; Audrey E. Carlson; Sarah M. Clinton; Georgia E. Hodes (Brain, Behavior, & Immunity - Health, 2024)
Stress has been implicated in the incidence and severity of psychiatric and gastrointestinal disorders. The immune system is capable of modulating the activity and composition of the gut following stress and vice versa. In this study we sought to examine the sequential relationship between immune signaling and microbiome composition occurring in male and female mice over time using a variable stress paradigm. Tissue was collected prior to, during, and after the stress paradigm from the same mice. Cytokines from plasma and brain were quantified using a multiplexed cytokine assay. Fecal samples were collected at the same timepoints and 16S rRNA amplicon sequencing was performed to determine the relative abundance of microbiota residing in the guts of stressed and control mice. We found sex differences in the response of the gut microbiota to stress following 28 days of chronic variable stress but not 6 days of sub-chronic variable stress. Immune activation was quantified in the nucleus accumbens immediately following Sub-chronic variable when alterations of gut composition had not yet occurred. In both sexes, 28 days of stress induced significant changes in the proportion of Erysipelotrichaceae and Lactobacillaceae, but in opposite directions for male and female mice. Alterations to the gut microbiome in both sexes were associated with changes in cytokines related to eosinophilic immune activity. Our use of an animal stress model reveals the immune mechanisms that may underly changes in gut microbiome composition during and after stress. This study reveals potential drug targets and microbiota of interest for the intervention of stress related conditions.